Diseases and fungicides in the production of onion seeds - Galli, José (Pesquisa Agropecuaria Brasileira, 2014)
From 1963 to 1968 a series of studies were carried out in an effort to control onion (Allium cepa L.) diseases, especially mildew and anthracnose, in the seed production stage, by the Section of Plant Pathology, IPEAS, Pelotas, Rio Grande do Sul, Brazil. Using a series of fungicides and with various frequencies of application (maximum of 30), significant differences were obtained between treatments, especially against mildew, in only two years. The differences, however, were not reflected in a manner that would permit conclusions regarding economic advantage of the treatment. In the text, other factors are also mentioned which aid in resolving the problem.